Implementing Disaster Simulation for Undergraduate Nursing Students - Eko Prasetya Widianto; Arista Maisyaroh; Rizeki Dwi Fibriansaridst; Syaifuddin Kurnianto; Candra Alif Novyanto (Universitas Bondowoso, 2022)
Background: Natural disasters are disasters caused by events or a series of events caused by nature, including earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes, and landslides. Earthquakes are the biggest natural disaster threat in Indonesia because they can occur suddenly and can occur in densely populated areas, such as big cities. The purpose of this study was to determine the effectiveness of the use of the simulation method in increasing the knowledge of nursing students in disaster preparedness. Method: The respondents were 55 nursing students. This research uses quasi-experimental with a one-group pre-post-test design to measure the level of knowledge of respondents using a questionnaire about disaster emergencies (pre-test). Respondent given intervention with simulation learning method about emergency disaster. They were re-measured using the same questionnaire (post-test). Result: Statistical test results using the Wilcoxon Signed-Rank Test showed that the value of p = 0.0001 was smaller than 0.05. It can be concluded that learning activities using the simulation method can increase students ' knowledge in disaster emergencies . Conclusion: The simulation learning method and disaster emergency skills training can improve students' understanding and skills in natural disaster preparedness.